2016
DOI: 10.1080/10942912.2016.1213281
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antioxidant activity of oil from wildAchillea setaceaandA. vermicularis

Abstract: The objective of this study was to determine and compare the composition of volatile components of two species, A. setacea and A. vermicularis, under the temperate climatic conditions (north of Iran) and to investigate quantification of fatty acids in the oil extracted using gas chromatography-flame ionization detector and to evaluate the antioxidant potential and the phytochemical profile in terms of phenolic acids and flavonoids content of the oils obtained from the plants. Gas chromatography-mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…Considering the results of GC/MS analysis performed for the studied species, piperitone (19.79 %), camphor (77.19 %), α ‐terpinene (22.28 %), eucalyptol (28.28 %), artemisia ketone (31.90 %), eucalyptol (22.89 %), endo ‐borneol (30.07 %), β ‐eudesmol (22.46 %), camphor (38.96 %), eucalyptol (37.44 %), camphor (16.55 %), verbenol (27.98 %), endo ‐borneol (73.05 %), camphor (18.87(%), β ‐eudesmol (29.17 %) and β ‐eudesmol (39.59 %) were found to be major components. The results of the study are in line with the literature . It can be said that the essential oil contents of Achillea species are affected by factors such as collection period, soil structure and climatic conditions.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Considering the results of GC/MS analysis performed for the studied species, piperitone (19.79 %), camphor (77.19 %), α ‐terpinene (22.28 %), eucalyptol (28.28 %), artemisia ketone (31.90 %), eucalyptol (22.89 %), endo ‐borneol (30.07 %), β ‐eudesmol (22.46 %), camphor (38.96 %), eucalyptol (37.44 %), camphor (16.55 %), verbenol (27.98 %), endo ‐borneol (73.05 %), camphor (18.87(%), β ‐eudesmol (29.17 %) and β ‐eudesmol (39.59 %) were found to be major components. The results of the study are in line with the literature . It can be said that the essential oil contents of Achillea species are affected by factors such as collection period, soil structure and climatic conditions.…”
Section: Resultssupporting
confidence: 87%
“…In another study, α ‐bisabolone oxide A (27.0 %) and hexadecanoic acid (16.4 %) were identified as major components . When we look at the latest study on this species, nerolidol (20 %) and cubebene (14 %) were identified as the main components . Our results are in parallel with the literature.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…In recent years, the antioxidant activity of important antioxidant compounds have been investigated. [21][22][23][24][25][26][27][28][29][30] In this section, the effects of NHMe, OMe, and tert-butyl substituents on the BDE and IP values of tyrosol were investigated, in order to find the novel tyrosol derivatives with high level of antioxidant activity. This work represents the first systematic study of antioxidant activity of substituted tyrosol derivatives by using of theoretical methods.…”
Section: Computed Bde and Ip Values Of Tyrosol Derivativesmentioning
confidence: 99%